PENGARUH WAKTU TEKAN DAN HASIL GUMPALAN TERHADAP KEKUATAN GESER PADA LAS TITIK - Nofriady Handra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2014)
Spot welding is actually used for body of car manufacture on automobile industry. The purpose of this research was to know the good time of pressure and the current of welding, especially for 1,5 mm sheet metal welding. The methods that were used in this study were, first of all, making of experiment of the strenght of the welding result, processing dat, analyzing data and making conclusion and report. After doing the research and getting the result, the good time of pressure and current used on 1,5 mm sheet metal was 10, 20 and 30 seconds and 70 Amp. Is was proven that after the shear tested for the pressure time 10 second and current 70 Amp. The result of treatment gotten was 488,658 N/mm2 , and for the pressure time 30 seconds and Amp, the shear strenght gotten was 510,593 N/mm2. . The data analysis the writer concluded that time of pressure and current were very insfluenntial on the result of the strenght of welding by using spot welding machine. It was because of the electrode pressure time of welding on the material would cause heat that making nugget. The heat processing will influence the result of welding extension.